Socio-pragmatic analysis of the film script based on discourse analysis of My Fair Lady - Grézlová, Eva (2007)
In my thesis I analyse speech behaviour of six characters from the film script of the musical My Fair Lady. Individual speakers have different speech habits on the basis of which certain social characteristics such as status, education, profession, or age can be derived. The aim of my diploma thesis is to study the ways of communicating and sociolinguistic parameters in the analyzed text